XYLOPERTHA REFLEXICAUDA (LESNE, 1937) A NEW SPECIES TO THE TURKISH FAUNA WITH A NEW PEST RECORD ON FIG IN TURKEY - Ozgen, Inanc; Hava, Jiri (Amer Entomol Soc, 2021)
This study was carried out in 2017 to detect populations of the xyllophagous fig pest Xylopertha reflexicauda (Lesne 1937) (Coleoptera: Bostichidae) in Diyarbakir Province of Turkey. This species has been determined to be a pest after culturing dead fig trees. This is the first report of its spread in Turkey, and the first reported damage to fig in Turkey. Features of the exit hole of the species and some feeding characteristics of the species are provided. This is an important addition to the fauna in Diyarbakir Province.
Keywords: Bostrichidae; Xylopertha reflexicauda; Feeding Behavior; New Record; New pest; Ficus carica; Turkey